Professional identity crisis : balancing the internal and external perception of professional image - Tomo, Andrea (Bingley, U.K. : Emerald Publishing Limited, 2019)
In a professional world that is quickly transforming and becoming increasingly volatile and uncertain, the nature of professional identity is complex and dynamic. The current literature has overlooked many issues concerning how professionals react and behave in the face of threats to their identity and image and there is a lack of a systemic analysis of the phenomenon of professional identity crisis. This book contends that a full comprehension of the dynamics taking place is now paramount from the individual perspective and provides a new theoretical and practical approach to the analysis and interpretation of these issues. Providing a novel understanding, the book delivers an empirical case to explore professionals' reactions in a context characterised by a sharp deprofessionalisation pattern and everexpanding regulation, uncertainty, and external pressures, which constrain and mould accountants' professional boundaries and activities. This book will prove a useful read to researchers across organisation studies, as well as interested professionals.
Prelims -- Introduction -- Professional identity: features and implications -- Professionals and identity crisis: a flexibility matter? -- Professionals' attempts to manage uncertainties and de-professionalization: the case of Italian accountants -- Conclusion -- References -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Professional employees; Professional ethics; Business & Economics -- General; Business & management